MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KONSEP BERIMAN KEPADA QADHA DAN QADAR MELALUI PEMBELAJARAN KOOPERATIF MODEL STAD DI KELAS VIA SDN 2 RAMPA KOTABARU - Siti Hadijah (STKIP Paris Barantai, 2022)
This class action research aims to determine the increase in student learning activities through cooperative learning of the STAD model of having faith in qadha and qadar in the classroom VIA SDN 2 Rampa Kotabaru. To find out the improvement of student learning outcomes through cooperative learning, the STAD model has faith in qadha and qodar. This study used classroom action research using cooperative learning of the STAD model which was carried out in 2 cycles. Each cycle consists of planning, implementing actions, observation and reflection. The techniques used in data collection in this study were observation and tests. Based on the results of data analysis; there was an increase in student activity in learning increased from 62.99% to 83.93%. Learning outcomes also increased from 66.67% to 83.33%, with average learning outcomes increasing to 72.83. The conclusion of this study is that the use of cooperative learning of the STAD model can increase the activities and learning outcomes of students with the concept of faith in qadha and, so that cooperative learning of the STAD model can be used as an alternative in the implementation of learning Islamic Religious Education and Ethics. Keywords: STAD Models, Activities and Learning Outcomes.